2018
DOI: 10.1007/s10620-018-5396-6
|View full text |Cite|
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Capsules with Targeted Colonic Versus Gastric Delivery in Recurrent Clostridium difficile Infection: A Comparative Cohort Analysis of High and Lose Dose

Abstract: Background Fecal microbiota transplantation (FMT) is an effective therapy for recurrent Clostridium. difficile infection (rCDI). FMT capsules have emerged and, it is unknown if delivery location and dose impacts efficacy. Methods We compared two cohorts of patients receiving two capsule formulations: gastric release (FMTgr) and targeted colonic release (FMTcr) at two different sites. Cohort A received FMTgr at 1) high dose: 60 capsules and low dose: 30 capsules. Patients in Cohort B received FMTcr at 1) high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 22 publications
4
42
0
1
Order By: Relevance
“…A key advantage of a pooled stool is that it increases the chances of transmitting key bacteria to the recipient; however, it is not clear whether this hypothesis is translated into real efficacy (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…A key advantage of a pooled stool is that it increases the chances of transmitting key bacteria to the recipient; however, it is not clear whether this hypothesis is translated into real efficacy (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The viabilities of approximately 90% were retained after these capsules were exposed to gastric environment for 2 h while the unencapsulated probiotics showed poor tolerance to the gastric environment [83]. Based on a comparative cohort analysis in patients, Allegretti et al [84] also demonstrated the effective colon-targeting of the fecal microbiota transplantation capsules coated with a blend of enzyme-triggered and pH-responsive polymers.…”
Section: Polysaccharide-based Systemsmentioning
confidence: 99%
“…The oral capsule proved almost as e cient as enema forms (− 3.8 dysbiotic days), even if the amount of administered bacteria was 100 times lower and required a longer administration period (1 week compared to two days). In previous studies, two approaches were mainly developed for FMT oral capsules, rst freezing at -80 °C with glycerol, then more recently freeze-drying with various cryoprotectants, as performed in the present study [41][42][43]. Interestingly, Jiang and colleagues (2017) [42] showed in mice that there was no difference in e ciency of frozen and lyophilized capsules in rCDI treatment, and that products can be stored up to 7 months without losing microbiota composition and therapeutic e cacy.…”
Section: Discussionmentioning
confidence: 82%
“…The effect of these two formulations was compared to that of a new caecumreleasing capsule containing a freeze-dried form of the enema formulation. Oral capsule is the most recently developed mode of stool delivery, the rst formulation being described in 2014 [40,41]. Capsules which are esthetically pleasing, convenient and minimally invasive are preferred by patients, and present the bene t to be the cheapest FMT mode of administration [18,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation